Minecraft the manga. 4 - Seto, Kazuyoshi (Viz Media, LLC, 2025)
"Peaceful life in a perfectly constructed town bores ten-year-old Nico into mischief. Riding creepers while they explode is fun and all, but what he really wants is to escape the blocky confines of hishome and take his crafting skills on an adventure to the end of theworld. Just how big is the world, anyway, and what could possibly stand in his way? Nico's journey, following his father to the end ofthe world, has reached a new level of intensity! He's gathered friends who adventure alongside him, explored a whole lot of the world, and helped a ton of people. What's next? What in the world is an Enderman?!"--